Ketogenic therapy for schizophrenia: evidence, mechanisms, and clinical perspectives - Cristiano Chaves; Cristiano Chaves; Jennifer Fabe; Fabiano A. Gomes; Heather McNeely; Massimo Tusconi; Mauro Giovanni Carta; Serdar M. Dursun; Serdar M. Dursun; Jaime E. C. Hallak; Jaime E. C. Hallak; Jaime E. C. Hallak; et al. (Frontiers in Pharmacology, 2025)
IntroductionSchizophrenia is a chronic psychiatric disorder marked by significant cognitive and functional impairments. Current antipsychotic treatments offer limited benefit for negative symptoms and cognitive dysfunction while often exacerbating metabolic comorbidities. Emerging evidence implicates impaired glucose metabolism and mitochondrial dysfunction in the pathophysiology of schizophrenia, suggesting a role for metabolic interventions.MethodsThis article reviews and synthesizes clinical, preclinical, and mechanistic evidence supporting the use of ketogenic therapy—a high-fat, low-carbohydrate intervention that induces ketosis—as a potential adjunctive treatment in schizophrenia.ResultsPreliminary clinical findings, including case reports and small trials, suggest that ketogenic therapy may improve positive and negative symptoms, cognitive performance, and metabolic outcomes in individuals with schizophrenia spectrum disorders. Preclinical studies using NMDA antagonist models demonstrate that ketogenic interventions can normalize behavioral and neurophysiological deficits. Mechanistically, ketone bodies enhance mitochondrial function, modulate neurotransmitter systems (GABA, glutamate, dopamine), and reduce inflammation and oxidative stress. These effects may address core dysfunctions in schizophrenia that are unresponsive to dopamine-targeting pharmacotherapies.DiscussionKetogenic therapy holds potential for addressing unmet clinical needs in schizophrenia, including negative and cognitive symptoms, treatment-resistant cases, and antipsychotic-induced metabolic syndrome. It may also be explored as a preventive strategy in high-risk populations. However, larger controlled trials are needed to establish efficacy, safety, and feasibility in psychiatric settings.ConclusionKetogenic therapy offers a novel, mechanistically informed intervention that targets metabolic and neurochemical pathways implicated in schizophrenia. If validated, it could pave the way for more integrative and personalized treatment strategies.